Chromosomal integration vectors allowing flexible expression of foreign genes in Campylobacter jejuni. Issue 1 (December 2015) - Jervis, Adrian; Butler, Jonathan; Wren, Brendan; Linton, Dennis
Abstract Background Campylobacter jejuni is a major cause of human gastroenteritis yet there is limited knowledge of how disease is caused. Molecular genetic approaches are vital for research into the virulence mechanisms of this important pathogen. Vectors that allow expression of genes inC. jejuni via recombination onto the chromosome are particularly useful for genetic complementation of insertional knockout mutants and more generally for expression of genes in particularC. jejuni host backgrounds. Methods A series of three vectors that allow integration of genes onto theC. jejuni chromosome were constructed by standard cloning techniques with expression driven from three different strong promoters. Following integration onto theC. jejuni chromosome expression levels were quantified by fluorescence measurements and cells visualized by fluorescence microscopy. Results We have created plasmid, pCJC1, designed for recombination-mediated delivery of genes onto theC. jejuni chromosome. This plasmid contains a chloramphenicol resistance cassette (cat ) with upstream and downstream restriction sites, flanked by regions of theC. jejuni pseudogene Cj0223. Cloning of genes immediately upstream or downstream of thecat gene allows their subsequent introduction onto theC. jejuni chromosome within the pseudogene. Gene expression can be driven from the native gene promoter if included, or alternatively from thecat promoter if the gene is cloned downstream of, and in the same transcriptional orientation ascat . To provide increased and variable expression of genes from theC. jejuni chromosome we modified pCJC1 through incorporation of three relatively strong promoters from theporA, ureI andflaA genes ofC. jejuni, Helicobacter pylori andHelicobacter pullorum respectively. These promoters along with their associated ribosome binding sites were cloned upstream of thecat gene on pCJC1 to create plasmids pCJC2, pCJC3 and pCJC4. To test their effectiveness, a green fluorescent protein (gfp ) reporter gene was inserted downstream of each of the three promoters and following integration of promoter-gene fusions onto theC. jejuni host chromosome, expression levels were quantified. Expression from theporA promoter produced the highest fluorescence, fromflaA intermediate levels and fromureI the lowest. Expression ofgfp from theporA promoter enabled visualization by fluorescent microscopy of intracellularC. jejuni cells following invasion of HeLa cells. Conclusions The plasmids constructed allow stable chromosomal expression of genes inC. jejuni and, depending on the promoter used, different expression levels were obtained making these plasmids useful tools for genetic complementation and high level expression.